2020
DOI: 10.1186/s12879-020-05630-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The risk factors of intracranial infection in patients with intracerebral hemorrhage undergone hematoma puncture: what should we care

Abstract: Background Intracranial infection after puncture of cerebral hematoma in patients with intracerebral hemorrhage is very common in the department of neurosurgery, yet the relevant risks remain unknown. We attempted to analyze the risk factors of intracranial infection after puncture of cerebral hematoma, to provide insights into the management of patients with intracerebral hemorrhage after puncture of cerebral hematoma. Methods Patients with intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…As one of the common complications after craniotomy, intracranial infection will not only prolong the hospital stay, but also increase the medical burden and even threaten the life and health of patients. erefore, in the early stage of craniotomy, it is of great significance to screen the risk factors of postoperative intracranial infection and take corresponding measures to reduce the incidence of intracranial infection and improve the prognosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the common complications after craniotomy, intracranial infection will not only prolong the hospital stay, but also increase the medical burden and even threaten the life and health of patients. erefore, in the early stage of craniotomy, it is of great significance to screen the risk factors of postoperative intracranial infection and take corresponding measures to reduce the incidence of intracranial infection and improve the prognosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Considering its hazards and high incidence (2–22% according to the published literature) [ 5 ], scholars have tried to build predictive models for EVD-associated intracranial infections and find prevention strategies. Zhang et al considered that ASA grades, length of hospital stay, consecutive operation, and prolonged surgery time may contribute to the occurrence of EVD-associated intracranial infections [ 18 ]. Yang and colleagues found that prolonged postoperative ICU stays, frequent CSF sampling, longer duration of EVD, and preoperative intubation were independent risk factors for EVD-associated intracranial infections [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another example is that the scalp wound is not removed in time after healing after operation, and the suture stump of subcutaneous fascia layer is too long, which leads to foreign body reaction; After surgical decompression of bone ap, poor suture of cap aponeurosis, imprecise suture of dura mater or imprecise suture of cortex can cause postoperative cerebrospinal uid leakage, which leads to brain tissue communicating with the outside world and easily invading pathogenic microorganisms [14] . Especially, the placement of ventricular drainage tube may lead to bacteria crawling or intracranial infection, and the drainage uid ows back to the brain, resulting in retrograde intracranial infection [15] . Finally, the second operation will lead to the accumulation of the above risk factors, which will directly lead to the increase of postoperative infection rate.…”
Section: Discussionmentioning
confidence: 99%